Immediate and Medium-Term Follow-Up of Patients with Obstructive Sleep Apnea Undergoing Pharyngeal and Nasal Surgery: A Pilot Study - Stefanini, Renato; Campanholo, Milena de Almeida Torres; Prescinotto, Renato; Caparroz, Fábio de Azevedo; Bittencourt, Lia Rita Azeredo; Tufik, Sergio; Haddad, Fernanda Louise Martinho (Sleep Science, 2023)
Objectives To evaluate the evolution of obstructive sleep apnea (OSA), comparing data from preoperative, immediate postoperative and late postoperative, in patients undergoing pharyngeal surgery associated with nasal surgery, and to compare the findings of arterial tonometry and type 1 polysomnography in the late postoperative period.Methods Seventeen adults with moderate or severe OSA were included in the study. They underwent clinical evaluation, surgical intervention, and sleep study preoperatively, on the 1st night after surgery, and after a minimum period of 3 months. The data for the three moments were compared.Results The mean age was 38.1 ± 12.5 years old (22 to 59 years old), and 82.3% were male. Body mass index (BMI) ranged from 25.6 to 45.1 kg/m2 (mean = 33.1 ± 5.8 kg/m2). Fifteen patients (88.2%) were diagnosed with severe OSA. There was a progressive improvement, with a decrease in the indexes (AHI and RDI) and in the percentage of time with peripheral oxyhemoglobin saturation below 90% (tSpO < 90%), and an increase in nadir of SpO2. In the comparison between the 2 methods used in the late postoperative period – arterial tonometry and polysomnography – there was no difference in the indexes and in the tSpO < 90%.Discussion There was a progressive and favorable impact of pharyngeal surgery on the improvement of polysomnographic and clinical respiratory parameters; however, many patients maintained residual OSA, suggesting the need for a new sleep study in the postoperative period. The arterial tonometry showed similar findings to polysomnography, which can be considered as an option in postoperative follow-up of patients.
Keywords: sleep apnea; obstructive/surgery; postoperative period; polysomnography; adult